TRP channels in epileptogenesis: calcium dysregulation mechanisms and pharmacological targeting strategies - Deng, Guolong; Liu, Dayuan; Zhong, Yunxiang; Wang, Muyao; Su, Baoshou; Jiang, Hongli; Zhai, Yihao; Peng, Hao; Zhang, Caicai; Feng, Jigao (Frontiers in Molecular Neuroscience, 2025)
Epilepsy, a prevalent neurological disorder affecting millions globally, manifests as recurrent synchronous neuronal discharges that disrupt normal cerebral function. Emerging evidence characterizes this condition as a network-level hyperexcitability disorder driven by aberrant neuroelectrical synchronization. At the molecular level, intracellular calcium (Ca2+) overload is increasingly recognized as a key contributor to seizure initiation and propagation. The regulation of neuronal Ca2+ homeostasis involves multiple Ca2+ − permeable cation channels, with transient receptor potential (TRP) channels emerging as critical mediators of pathological ion flux. These non-selective transmembrane conduits facilitate Ca2+ permeation and contribute to epileptogenic ionic dysregulation through subtype-specific mechanisms. Current research efforts focus on elucidating TRP channel pathophysiology across epilepsy subtypes while identifying potent pharmacological modulators. This systematic investigation of TRP channel biology and targeted therapeutic development promises to revolutionize antiepileptic drug discovery by addressing current treatment limitations in seizure prevention and disease modification. The present review synthesizes recent advances in TRP channel research and evaluates emerging strategies for therapeutic targeting in epilepsy management.